First record of Indolestes cyaneus (Selys, 1862) from Vietnam and notes on its color variation (Odonata: Zygoptera: Lestidae) - Phan, Quoc Toan; To, van Quang; Payra, Arajush (Zootaxa, 2019)
First record of Indolestes cyaneus (Selys, 1862) from Vietnam with providing illustrations of its detailed structures, as well as notes on the coloration of the populations from Taiwan, Nepal and India.